Male excess mortality during the epidemiological transition: theory and evidence from India - Astrid Krenz; Holger Strulik (Journal of Population Economics, 2025)
At any given age, adult men die at a higher rate than women. In many developed countries, increasing excess mortality of men has been demonstrated for cohorts born in the late nineteenth century and thereafter. The decline in infectious diseases is believed to have contributed to the increase in male excess mortality. Here, we focus on India during 1990–2019, a period in which the Indian states experienced, to varying degrees, the epidemiological transition. We show that male excess mortality evolves positively over the observation period, is greater in later-born cohorts, and is strongly associated with the decline in infectious disease mortality. We propose a simple theory that explains these facts by a greater influence of infections on the biological aging of women compared to men. We calibrate the model with Indian data and show that it can replicate the feature of rising male excess mortality over time and birth year of cohorts.
Keywords: I15; J11; J16; N35; 330; Male excess mortality; Epidemiological transition; Biological aging; India